John Wayne in the Irvine Ranch Farmers Market. Issue 3 (November 2015) - Sutton, Timothy
The Western as a Hollywood film genre was born in and of California, as was I. This piece was "triggered" by a memory of an encounter with John Wayne in a market as a young child. Recognizing how (Western) stories can hold us in their grip, this is the beginning of a larger project of deconstructing my Western narrative to perform new articulations into being. I use the question, "Why don't I speak Spanish?" as the entry point to begin to unravel the tangled legacy of colonialism in California (and the United States) and to locate my body within it. This is a performance (auto)ethnography that combines bricolage with ethnodrama in the form of a screenplay. In this way, I highlight and echo the mediated, filmic origin of the mythical West(ern).